Customized Prevention Trials Could Resolve the Controversy of the Effects of Omega-3 Fatty Acids on Cancer. (17th February 2020) - El-Bayoumy, Karam; Manni, Andrea
Abstract: Literature data revealed that the benefits of consuming omega-3 fatty acid (n-3FA) supplements such as fish oil with the goal of reducing the incidence of chronic diseases such as cardiovascular disease and cancer remain controversial. The purpose of this commentary is to discuss factors that may account for the inconsistency of results across different studies. Critical review of the published data, including our own preclinical and clinical studies, strongly suggests that customized clinical prevention trials are needed to resolve the above-mentioned controversy. Specifically, in order to develop a personalized cancer prevention strategy, more attention should be given to multiple factors including the dose of the n-3FA, the specific placebo used as a comparator, duration of administration, type of intervention (primary vs secondary prevention trial), specific compound (DHA vs EPA vs their metabolites), the ratio of n-3FA:n-6FA and the target population tested (high vs average risk).